Heparan sulfate proteoglycans serve as alternative receptors for low affinity LCMV variants. - André Volland (Public Library of Science (PLoS), 2021)
Members of the Old World Arenaviruses primarily utilize α-dystroglycan (α-DAG1) as a cellular receptor for infection. Mutations within the glycoprotein (GP) of lymphocytic choriomeningitis virus (LCMV) reduce or abrogate the binding affinity to α-DAG1 and thus influence viral persistence, kinetics, and cell tropism. The observation that α-DAG1 deficient cells are still highly susceptible to low affinity variants, suggests the use of an alternative receptor(s). In this study, we used a genome-wide CRISPR Cas9 knockout screen in DAG1 deficient 293T cells to identify host factors involved in α-DAG1-independent LCMV infection. By challenging cells with vesicular stomatitis virus (VSV), pseudotyped with the GP of LCMV WE HPI (VSV-GP), we identified the heparan sulfate (HS) biosynthesis pathway as an important host factor for low affinity LCMV infection. These results were confirmed by a genetic approach targeting EXTL3, a key factor in the HS biosynthesis pathway, as well as by enzymatic and chemical methods. Interestingly, a single point mutation within GP1 (S153F or Y155H) of WE HPI is sufficient for the switch from DAG1 to HS binding. Furthermore, we established a simple and reliable virus-binding assay, using directly labelled VSV-GP by intramolecular fusion of VSV-P and mWasabi, demonstrating the importance of HS for virus attachment but not entry in Burkitt lymphoma cells after reconstitution of HS expression. Collectively, our study highlights the essential role of HS for low affinity LCMV infection in contrast to their high affinity counterparts. Residual LCMV infection in double knockouts indicate the use of (a) still unknown entry receptor(s).